Lactobacillus johnsonii HL79 modulates the microbiota-gut-brain axis to protect cognitive function in mice chronically exposed to high altitude - Zhao, Zhifang; Zhang, Xufei; Sun, Ning; Duan, Lixiao; Xin, Jinge; Li, Hao; Ni, Xueqin; Wang, Hesong; Ma, Hailin; Bai, Yang (Frontiers in Microbiology, 2025)
IntroductionHigh-altitude environments have significant effects on brain function, particularly a decline in cognitive function, due to insufficient oxygen supply. The microbiome-gut-brain axis (MGBA) plays an important role in regulating cognitive function, but its specific mechanism of action in high-altitude environments is unclear. Therefore, the aim of this study was to investigate whether the probiotic Lactobacillus johnsonii HL79 could alleviate high altitude-induced cognitive dysfunction in mice by modulating the gut microbiota.Methods and resultsSixty C57BL/6 mice aged 8 weeks were randomly divided into four groups: control, high altitude exposure (HA), HL79-treated (P), and high altitude exposure plus HL79-treated (HAP). the HA and HAP groups were exposed to a low-pressure oxygen chamber at a simulated altitude of 3,500–4,000 m for 20 weeks, while the Control and P groups were maintained at the normal barometric pressure level. Probiotic HL79 was given daily by gavage in the P and HAP groups, while saline gavage was given daily in the other two groups. The cognitive functions of the mice were assessed by new object recognition test and elevated plus maze test. The results showed that HL79 treatment significantly improved the working memory abilities of high altitude exposed mice. In addition, HL79 treatment improved antioxidant capacity, decreased malondialdehyde (MDA) content, and increased superoxide dismutase (SOD) and catalase (CAT) activities in serum and whole brain tissue. Gut microbiota analysis showed that HL79 was able to modulate the structure of gut microbiota and increase the relative abundance of beneficial flora in high altitude environment.ConclusionLactobacillus johnsonii HL79 significantly ameliorated cognitive dysfunction in high altitude-exposed mice by modulating the gut microbiota and antioxidant capacity, further confirming the important role of MGBA in high altitude environment.